Shear-induced acquired von Willebrand syndrome: an accomplice of bleeding events in adults on extracorporeal membrane oxygenation support - Wang, Haiwang; Li, Duo; Chen, Yuansen; Liu, Ziquan; Liu, Yanqing; Meng, Xiangyan; Fan, Haojun; Hou, Shike (Frontiers in Cardiovascular Medicine, 2023)
Extracorporeal membrane oxygenation (ECMO) is an increasingly acceptable life-saving mechanical assistance system that provides cardiac and/or respiratory support for several reversible or treatable diseases. Despite important advances in technology and clinical management, bleeding remains a significant and common complication associated with increased morbidity and mortality. Some studies suggest that acquired von Willebrand syndrome (AVWS) is one of the etiologies of bleeding. It is caused by shear-induced deficiency of von Willebrand factor (VWF). VWF is an important glycoprotein for hemostasis that acts as a linker at sites of vascular injury for platelet adhesion and aggregation under high shear stress. AVWS can usually be diagnosed within 24 h after initiation of ECMO and is always reversible after explantation. Nonetheless, the main mechanism for the defect in the VWF multimers under ECMO support and the association between AVWS and bleeding complications remains unknown. In this review, we specifically discuss the loss of VWF caused by shear induction in the context of ECMO support as well as the current diagnostic and management strategies for AVWS.